Legal Aıd For Cıvıl Servants In Corruptıon Cases Related To Equıtable Procurement Of Goods/Servıces - Kemilau Mutik; Abdul Rachmad Budiono; Yohanes Sogar Simamora; Moh. Fadli; Shinta Hadiyantina (Cita Konsultindo Research Center, 2024)
In the context of legal science, the value of justice for all Indonesian people as stated in Pancasila, the 5th Precept is termed as substantive justice, namely justice that is actually felt by the community and created through legal formation. In these precepts, the essence of justice is based on and imbued with justice in the life of the nation, justice towards the creator and fellow human beings. Laws in Indonesia must be in line with Pancasila. Equitable law enforcement means that every community must get equal treatment before the law (equality before the law) and fair or access to justice, especially civil servants in carrying out their duties and obligations as government officials. Legal aid has an important position in every criminal justice system and helps to achieve a